2013
DOI: 10.1002/anie.201306511
|View full text |Cite
|
Sign up to set email alerts
|

A Traceless Directing Group for CH Borylation

Abstract: N-borylation of nitrogen heterocycles and anilines provides a traceless directing group for subsequent catalytic C–H borylations. Selectivities that previous required Boc protection can be realized with the advantages that the NBpin directing group can be installed and removed in situ and product yields improve substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
140
1
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(163 citation statements)
references
References 29 publications
(32 reference statements)
6
140
1
16
Order By: Relevance
“…Smith and Maleczka have recently shown that the N-H group of various heterocycles can be temporarily protected by N-H borylation with HBpin. 12 However, we were not able to achieve the borylation of indazole following this protocol. Consequently a series of different, less labile, nitrogen protecting groups were explored ( Table 1).…”
Section: Figure 1 C-h Borylation Of 2-fluoropyridinesmentioning
confidence: 93%
“…Smith and Maleczka have recently shown that the N-H group of various heterocycles can be temporarily protected by N-H borylation with HBpin. 12 However, we were not able to achieve the borylation of indazole following this protocol. Consequently a series of different, less labile, nitrogen protecting groups were explored ( Table 1).…”
Section: Figure 1 C-h Borylation Of 2-fluoropyridinesmentioning
confidence: 93%
“…The reaction at the 4-position of pyrazoles results from borylation of the nitrogen, creating steric hindrance around the nonbasic nitrogen of this heterocycle, and a presumed higher barrier for C−H bond cleavage α to the basic nitrogen, as is seen in pyridine. 111,140 …”
Section: Arene Functionalization Without Directing Groupsmentioning
confidence: 99%
“…cross-coupling reaction, 8 Marder's Cu-catalyzed borylation reaction, 9 Maligre's Ir-catalyzed C−H bond activation reaction, 10 Hsu's aryl Grignard reagents or aryllithium species with trialkyl boronates, 11 Wang's transition-metal-free transformation from aromatic amines. 12 Although these procedures have shown some practical applications in synthesis, their application on a preparative scale has still been limited and deficient in view of laborious synthetic process, harsh reaction conditions, heavy metal contamination, with the result that it is difficult to meet the demands for large-scale preparation.…”
mentioning
confidence: 99%